The use of the language laboratory in a Federal University: reflections on the relevance of using the language lab for English learners - CARVALHO, Beatriz Batista (2023)
Currently, with the support of the internet and the new digital information and communication technologies (NICS), such as smartphones and computers, students have the opportunity to enjoy a series of services that can help their learning process, such as social media, chats, interactive materials and others. In this way, technological resources have been helping the learning of the English language and demonstrating several benefits for students. Therefore, this research aims at identifying the reasons that collaborate to the fact that the language laboratory is underused by the students of the course, besides highlighting the benefits that the space offers to the students' learning process and, based on the results presented, contributing to a better use of the available resources. For this, the research was based on the theories of Moran (2000), Gomes and Moita (2016) who analyze the importance of technology in education; in Oliveira (2008) who conceptualizes autonomy and how to foster it in language classes, as well as other authors. To achieve the purpose of this study, a qualitative research of the case study type was conducted, which involved data collection through an online questionnaire, realized with the students of the English language course at UFPA. As a result, it was observed that the language lab favors the autonomy of English learning, offers a propitious place for practicing and improving language skills, provides access to technological resources that help develop learning in an independent and interactive way, and other benefits.